General education biology labs: a Delphi study of student learning outcomes - Dayna Jean DeFeo; Sarah Gerken; Trang C. Tran; Dmitry Khodyakov; Arlene Fink (Discover Education)
Abstract Introductory biology courses at most colleges and universities have two components: a lecture and a lab. However, for students who are not majoring in biology and taking the introductory course as part of their general education requirements, the distinct role of the lab has not been clearly articulated. We performed an online modified-Delphi study of student learning outcomes (SLOs) for non-majors biology. We engaged 73 biology faculty experts from institutions across the US in four iterative rounds to identify, rate, discuss, and re-rate ten SLOs for non-majors biology labs on the dimensions of importance, feasibility, and distribution of responsibility between lab and lecture. On average, the panel achieved consensus around eight SLOs as “important.” All of the SLOs were rated as “feasible” under optimal teaching and learning contexts, but the panelists noted that current institutional constraints render some as less feasible. Our analysis suggests that labs share many SLOs with lectures, but there are also some SLOs that are unique to the lab. Our study provides recommendations for coordinated strategies and efforts between lecture and lab activities to promote more rigorous learning and better attainment of those outcomes.